Penyalahgunaan Senjata Tajam Oleh Masyarakat Adat - Ratu Boi Maira Suat Pasai; Reimon Supusepa; Iqbal Taufik (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Prohibited acts other than firearms and explosives include those that are not firearms because it is prohibited to carry bats, stabbing and stabbing tools.Purposes of the Research: To describe the abuse and the factors that hinder the legal handling of sharp weapons by indigenous peoples. Methods of the Research: This research method is a type of empirical juridical research, or called field research, examining applicable legal provisions, and its actual actions that occur in society itself.  Results of the Research: Misuse of sharp weapons by Indigenous Peoples in Waesama Subdistrict, South Buru Regency and the occurrence of murder cases due to carrying sharp vessels in the form of machetes in the general environment of the community, saying that "carrying sharp weapons has become their habit for generations, which is always carried wherever they travel both in the forest and the general environment of the community and part of their activity. The factors hindering the legal handling of sharp weapons abuse in Waesama District, South Buru Regency, are caused by internal and external factors. Internal factors are the existence of a habit that is cultivated, the curator of awareness and knowledge of indigenous peoples is lacking. Meanwhile, extenal factors are religious and educational factors.